La voûte de la justice et le mur de la bienveillance : deux formes du lien social selon David Hume - Éléonore Le Jallé (Astérion)
Commenting David Hume’s metaphor of the “wall” of benevolence and the “vault” of justice in the third Appendix of his Enquiry Concerning the Principles of Morals, the paper compares those two “social virtues”, and thus describes two forms of social links, corresponding respectively to the “natural virtue” of benevolence and to the “artificial virtue” of justice. I also examine Hume’s enhancing of the possible contradictions between those two virtues, when he remarks that some isolated acts of justice, though absolutely necessary to the cohesion of the “vault” of justice, actually constitute a “form of evil”; an observation that other authors such as Francis Hutcheson, Adam Smith and John Rawls, have somehow neglected.